2019
DOI: 10.7575/aiac.ijels.v.7n.2p.94
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Consequences of Streetism among Street Children in Harar City, Ethiopia

Abstract: The purpose of this study was to investigate the life of Harar City street children. In view of that, the following research questions were forwarded; what are the major causes that make children leave their homes for the streets? Do street children use psychoactive substances? What type of psychoactive substance do street children use? Based on these basic questions, descriptive survey design including quantitative and qualitative data gathering approaches were employed. Questionnaires and interviews were thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…The study found that the 10-years civil war and the 2015's earthquake destructed homes, killed and displaced thousands of families that ultimately increased the number of orphans and homeless children. Endris & Sitota (2019) argued that freedom and natural disaster work as other causes. They also explained that children often want to free from each time and entire home network UNICEF (1994) stated that the attraction of street life is increased by viewing other child's activities: playing, dancing, and enjoying at the place of the street.…”
Section: Causes Of Street Childrenmentioning
confidence: 99%
“…The study found that the 10-years civil war and the 2015's earthquake destructed homes, killed and displaced thousands of families that ultimately increased the number of orphans and homeless children. Endris & Sitota (2019) argued that freedom and natural disaster work as other causes. They also explained that children often want to free from each time and entire home network UNICEF (1994) stated that the attraction of street life is increased by viewing other child's activities: playing, dancing, and enjoying at the place of the street.…”
Section: Causes Of Street Childrenmentioning
confidence: 99%
“…Intervention and corrective measures were not taken by the government as well as other non-governmental organizations. Researches also support it for example (10) says that the number of children on the street is increasing and the children are vulnerable to various problems from time to time.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…These reasons are family violence, abuse, parental alcoholism, poverty, and parental mortality due to HIV and AIDS (9). In developing countries, many children are left alone on account of losing their parents for sexually transmitted diseases such as HIV ADIS, famine, conflict, war, and so forth which finally end up children's life in the streets (10).…”
Section: Background Of the Studymentioning
confidence: 99%
“…At the first level, termed microsystems, is the interaction of a street child with people who have the strongest influence on his or her development, such as parents and siblings. In the case of Khartoum's street children, the push factor for a child's decision to be on the street is mainly economic hardship and poverty, relationship problems with stepparent and violence in the household (Kudrati, Plummer & Yousif, 2008;Abdelmoneium, 2017;Endris & Sitota, 2019). Ansell (2016) discovers that to escape from troubles at home, children moved to the streets and the aftermath of living on the streets intensifies their incompetence to ensure better livelihoods.…”
Section: Introduce the Problemmentioning
confidence: 99%